LEGAL PROTECTION AGAINST A DEBTOR IN THE IMPLEMENTATION OF THE FIDUCIARY GUARANTEE EXECUTION PROCEDURE - Samsul Arifin; Putri Dwi Saadah (Universitas Muhammadiyah Metro, 2018)
The implementation of the fiduciary guarantee execution is settled in the Article 29 till the Article 34 Law No. 42 of 1999 on fiduciary guarantee, but in practice still cause legal issue, for example in the implementation of the fiduciary guarantee execution, creditor does against the law in a way taken forcibly that become the fiduciary guarantee object without showing the certificate of fiduciary guarantee. While in the procedure execution, at the time of the fiduciary guarantee execution shows the certificate of fiduciary guarantee. Legal issue that will be the writer discusses in this paper is the legal protection against a debtor in the implementation of the fiduciary guarantee execution procedure conducted in against the law by the creditor. The writing of legal method uses normative juridical approach namely invested against the positive law related to the effectiveness of the legislation. Legal protection for debtor in the fiduciary guarantee execution by filed a lawsuit to state court in the basis of against the law that has been done by creditor.